Critical Discourse Analysis in the Reporting of the NTT Governor's School Entry Hours Policy Controversy - Hakim, Lukman; Azzahro, Annisa Fitria; Hidayat, Mansur; Ardhinda, Selvira Diva (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2024)
This essay discusses the construction of the news about implementing school entry rules for Senior High Schools (SMA), issued by the Governor of East Nusa Tenggara (NTT), Viktor Laiskodat, on kompas.com. This study uses a descriptive-qualitative approach with Norman Fairclough's critical discourse analysis model. To conclude from the research that has been conducted, kompas.com highlights the controversy arising due to such a policy implemented by the Governor of NTT regarding school entry time rules. In addition, kompas.com also compiles its news neutrally by presenting various viewpoints with pros and cons. The problem context highlighted by kompas.com is processed through a text writing strategy that uses a light and short language structure appropriate to social reality and accessible for the public to understand. Kompas.com also describes assorted realities that emerge with various titles but retain the same theme about the reported problem.